2017
DOI: 10.1002/bmc.4123
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of usnic, diffractaic, evernic and barbatic acids in rat plasma by ultra‐high‐performance liquid chromatography–quadrupole exactive Orbitrap mass spectrometry and its application to pharmacokinetic studies

Abstract: Usnea longissima Ach. (Usnea) is used in pharmaceuticals, food and cosmetics. Evernic acid (EA), barbatic acid (BA), diffractaic acid (DA) and usnic acid (UA) are the most typical ingredients in U. longissima and exert a wide variety of biological functions. The study aimed to develop a sensitive method for simultaneous analysis of EA, BA, DA and UA in rat plasma and was applied to pharmacokinetic studies after consumption of UA and ethanol extract from U. longissima (UE). The samples were separated on a BEH C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The pharmacokinetic parameters obtained from compartmental and noncompartmental models were close and the bioavailability was about 77.8%. The pharmacokinetic behavior of usnic acid and phenolic acids, such as barbatic acid, diffractaic acid, and evernic acid, was studied in vivo in another study after intravenous and oral administration of pure usnic acid and extract from U. longissima ; the results showed that the absolute bioavailability of usnic acid was 69.2% and 146.9% after oral administration of usnic acid and ethanolic extract, respectively [ 147 ], indicating that the other coexisting ingredients in the extract can promote the absorption of usnic acid or inhibit its metabolism and elimination, thus, affecting its pharmacokinetic behavior in vivo.…”
Section: Metabolism and Pharmacokinetics Of Usnic Acid In Vivo And In...mentioning
confidence: 99%
“…The pharmacokinetic parameters obtained from compartmental and noncompartmental models were close and the bioavailability was about 77.8%. The pharmacokinetic behavior of usnic acid and phenolic acids, such as barbatic acid, diffractaic acid, and evernic acid, was studied in vivo in another study after intravenous and oral administration of pure usnic acid and extract from U. longissima ; the results showed that the absolute bioavailability of usnic acid was 69.2% and 146.9% after oral administration of usnic acid and ethanolic extract, respectively [ 147 ], indicating that the other coexisting ingredients in the extract can promote the absorption of usnic acid or inhibit its metabolism and elimination, thus, affecting its pharmacokinetic behavior in vivo.…”
Section: Metabolism and Pharmacokinetics Of Usnic Acid In Vivo And In...mentioning
confidence: 99%
“…Although there are many studies on the chemical constituents of “Dogel ebs” , at present, it is essential to obtain its pharmacokinetic parameters and metabolism information to fully understand the pharmacological effects and mechanism of “Dogel ebs.” Unfortunately, the identification of metabolites and illustration of its metabolic patterns have not yet been studied, except the pharmacokinetics investigations on matrine , which restricted the therapeutic applications and development of “Dogel ebs.” In order to clarify the metabolic mechanism of “Dogel ebs,” a target‐group‐change couple with mass defect filtering strategy was proposed based on high performance liquid chromatography–quadrupole exactive Orbitrap mass spectrometry (HPLC‐Q‐Exactive/MS) and Compound Discoverer software. As previously reported , Compound Discoverer software could provide elemental composition assignment, exact mass measurement, and fragmentation information in Traditional Chinese medicines and their metabolites in biological matrices . The metabolic pathway of the metabolites could be confirmed by the group change of prototype, which was called target‐group‐change technology.…”
Section: Introductionmentioning
confidence: 92%
“…A total of 16 amino acids and four derivatives were characterised based on fragmentation rules, database search, and relevant literature. 19,[30][31][32][33][34] Amino acid is a class of organic compounds containing…”
Section: Structural Characterisation Of Amino Acids and Derivativesmentioning
confidence: 99%